2016
DOI: 10.1108/ijph-04-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Routine or targeted HIV screening of Indonesian prisoners

Abstract: In a resource limited setting like Indonesia, routine HIV screening in prison is feasible and more effective than targeted screening, which may be stigmatizing. HIV infections that remain unrecognized can fuel ongoing transmission in prison and lead to unnecessary disease progression and deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Seven studies reported opt-out testing conducted during this process [8, 37, 38, 45, 46, 48]. Seven other articles reported testing taking place anywhere between 3 and 14 days after first reception, often during a secondary health check [39, 40, 44, 49–52]. Testing at a secondary clinic often occurred because of a perceived lack of time during the first night or because the first night health check was reserved for dealing with urgent healthcare problems that required immediate intervention [39, 40, 44, 49–52].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies reported opt-out testing conducted during this process [8, 37, 38, 45, 46, 48]. Seven other articles reported testing taking place anywhere between 3 and 14 days after first reception, often during a secondary health check [39, 40, 44, 49–52]. Testing at a secondary clinic often occurred because of a perceived lack of time during the first night or because the first night health check was reserved for dealing with urgent healthcare problems that required immediate intervention [39, 40, 44, 49–52].…”
Section: Resultsmentioning
confidence: 99%
“…Seven other articles reported testing taking place anywhere between 3 and 14 days after first reception, often during a secondary health check [39, 40, 44, 49–52]. Testing at a secondary clinic often occurred because of a perceived lack of time during the first night or because the first night health check was reserved for dealing with urgent healthcare problems that required immediate intervention [39, 40, 44, 49–52]. In a prison that has a rapid population turn-over (C), a programme mandated delay in engaging intake with an opt-out test offer (MR) reduces the proportion of intake offered a test (O), as some individuals have already been released or transferred (C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both facilities are extremely overcrowded and HIV prevalence rates are higher compared to prisons in other parts of the country [57]. HIV testing is offered to all persons during intake into jails and also at the request of inmates [58]. Persons diagnosed with HIV may access ART at no cost through prison-based HIV subspecialty clinics located within each prison.…”
Section: Study Settingmentioning
confidence: 99%